Developmental neuroanatomy of the rosy bitterling Rhodeus ocellatus (Teleostei: Cypriniformes)—A microCT study. Issue 12 (25th April 2022) - Yi, Wenjing; Mueller, Thomas; Rücklin, Martin; Richardson, Michael K.
Abstract: Bitterlings are carp‐like teleost fish (Cypriniformes: Acheilanathidae) known for their specialized brood parasitic lifestyle. Bitterling embryos, in fact, develop inside the gill chamber of their freshwater mussel hosts. However, little is known about how their parasitic lifestyle affects brain development in comparison to nonparasitic species. Here, we document the development of the brain of the rosy bitterling, Rhodeus ocellatus, at four embryonic stages of 165, 185, 210, 235 hours postfertilization (hpf) using micro‐computed tomography (microCT). Focusing on developmental regionalization and brain ventricular organization, we relate the development of the brain divisions to those described for zebrafish using the prosomeric model as a reference paradigm. Segmentation and three‐dimensional visualization of the ventricular system allowed us to identify changes in the longitudinal brain axis as a result of cephalic flexure during development. The results show that during early embryonic and larval development, histological differentiation, tissue boundaries, periventricular proliferation zones, and ventricular spaces are all detectable by microCT. The results of this study visualized with differential CT profiles are broadly consistent with comparable histological studies, and with the genoarchitecture of teleosts like the zebrafish. Compared to the zebrafish, our study identifies distinct developmental heterochronies in the rosy bitterling, such as a precocious development of the inferior lobe. Abstract : Rosy bitterling brain at 165 hours postfertilization. Tissue boundaries, periventricular proliferation zones, and ventricular spaces are all detectable by microCT in this very early stage. Three‐dimensional visualization with microCT scanning protocols is extremely useful for the study of the rosy bitterling and provides an updating of imaging modalities for morphological and anatomical analyses in this nonmodel organism.